Advancing applied pharmaceutical technology: A paradigm shift toward sustainable innovation and interdisciplinary convergence - Dipankar Ghosh (Journal of Applied Pharmaceutical Science, 2025)
No abstract is available.
Keywords: Applied Pharmaceutical Technology, Sustainable Innovation, Interdisciplinary Research, Green Chemistry, Biopharmaceuticals